DIVERSITAS GENDER PADA DEWAN DAN KINERJA PERUSAHAAN - Hendra Wijaya (Program Studi Akuntansi FPEB UPI, 2022)
This study aims to analyze the diversity of the board of commissioners and the diversity of the board of directors on the firm's performance.. The sample in this company is a non-financial company listed on the Indonesia Stock Exchange in 2015-2019. The sample in this study consisted of 259 companies and 1194 observations. Diversity on the board is measured using three proxies, namely the Blau index, the proportion of women on the board, and a dummy variable. Firm performance is measured by using three proxies, namely return on assets, return on equity, and return on sales. The results of this study indicate that diversity on the board of commissioners and diversity on the board of directors has no effect on company performance and consistency is indicated by using all measurements. This research has a contribution to the relationship of gender diversity on corporate governance and financial performance of non-financial firms in Indonesia.